2005
DOI: 10.1002/bmc.540
|View full text |Cite
|
Sign up to set email alerts
|

Nobiletin: efficient and large quantity isolation from orange peel extract

Abstract: It is known that nobiletin possesses anticancer, antiviral and anti-inflammatory activities. Recently, the demand for nobiletin in large quantities and high purity has increased. However, conventional normal-phase silica gel chromatography and C 18 -reverse-phase separation methods cannot satisfy the requirement of pure and gram scale nobiletin in a timely manner. In exploring the composition and the biological activities of polymethoxyflavones from sweet orange (Citrus sinensis) peel, we developed an efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 18 publications
2
34
0
1
Order By: Relevance
“…Indeed, the fact that the hydrophobic nature of the polymethoxy flavones enables them to cross the intestinal membrane easily, and makes them absorbed more readily into the human body (Li, Wang, Sang, Huang, & Ho, 2006). These results indicate polymethoxy flavones to be promising therapeutic phytochemicals of citrus by-products (Li, Yu, & Ho, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the fact that the hydrophobic nature of the polymethoxy flavones enables them to cross the intestinal membrane easily, and makes them absorbed more readily into the human body (Li, Wang, Sang, Huang, & Ho, 2006). These results indicate polymethoxy flavones to be promising therapeutic phytochemicals of citrus by-products (Li, Yu, & Ho, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Polymethoxylated flavones play a role in anticancer and anti-inflammation, as well as in atherosclerosis, cardiovascular dysfunction, and Alzheimer's disease in rats and humans [3,4,31]. Nobiletin is a well-known traditional Chinese medicine or food, and has antitumor, immune stimulation, anti-inflammation, antioxidant, and cardiovascular disease-mitigating properties [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Nobiletin is a well-known traditional Chinese medicine or food, and has antitumor, immune stimulation, anti-inflammation, antioxidant, and cardiovascular disease-mitigating properties [3,4]. Recent studies revealed that nobiletin, a clock-enhancing natural polymethoxylated compound, activates ROR nuclear receptors and protects against metabolic syndrome in a clock-dependent manner [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given their biological properties, a rapid, large-scale procedure for separating PMFs is needed (Li, Yu, & Ho, 2006;Raman, Jayaprakasha, Cho, Brodbelt, & Patil, 2005;Wang et al, 2005). It has been reported that Citrus sunki Hort.…”
Section: Introductionmentioning
confidence: 99%